Computer Aided Model for a Low Voltage Varistor with Increased Thermal Stability - Adrian F. Olariu; Flaviu M. Frigura-Iliasa; Florin I. Balcu; Mihaela Frigura-Iliasa; Lia Dolga; Hannelore Filipescu (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Metal Oxide Varistors are a very common power electronic device, applied for efficient overvoltage protection at any voltage level. This piece of equipment has a high non-linear current response function of the applied voltage, and, it provides a relatively high heat absorption capacity in case of accidental overvoltage pulse (shock)s. The crossing response current is clearly activated by temperature of that device, and, by consequent, overheating could be disastrous. Actual researches must be carried out both for a new more performant material as well as for new technical solutions for the design of all equipment integrating them, by studying heat extraction and heat transfer inside a new complex varistor device. Our article proposes a totally new device, used basically for low voltage applications, having a supplementary metal mass added to the body of that varistor, shaped as small disk. It actions like a heat pump immediately after the voltage pulse (shock) and as additional radiators at the end of the heating process caused by a transitory overvoltage. A CAD solution combined with a finite element model, followed by some experimental results are also presented, for confirming the performance of that newly design. By placing additional metal alloy masses inside a new varistor structure it will have a higher heat pumping and dissipation capability, in order to reduce temperature stress and all aging effects.